Peran Kyai dalam Pengembangan MSDM - Sumpena, Deden; Dewi, Ratna; Kurniawan, Muh. Idham (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
Da'wah, especially billisan has a significant role in making changes in society. Kyai as Dai, becomes central in these changes. The objectives of this research include: Examining the figure of the Dai, Muhyiddin Abdul Qodir Al-Manafi, How the Da'i Concept is in developing community resources, and, How it is the Implementation in developing community resources. The method used by researchers in this study is the descriptive method. The research results include the following. First: Muhyiddin is a figure of Kyai who was born and grew up in a family of scholars and has a lineage that is connected to the Prophet Muhammad. Second: reviving the sunnah, then developing it with the emphasis on building ukhuwah Islamiyyah and third: carrying out various activities or Community Resource Development movements to build, and strengthen understanding and practice of religion that is equitable for all levels of society. The impact of this research can be a basis for preaching that focuses on developing human resources.